Pengaruh metode computational thingking terhadap kemampuan berfikir kritis siswa kelas V sekolah dasar - Reka Nur Asmah; Nurul Hasanah; Elfi Lailan Syamita Lubis (Didaktika Dwija Indria, 2025)
The purpose of this study was to determine the effect of the computational thinking method on the critical thinking skills of fifth grade students of SD Negeri 050674 Bingai. The form of this research is a quasi-experimental study with a nonequivalent control group design. The data collection technique is a measurement technique and the data collection tool is a test in the form of an essay test. Pre-test data were analyzed using the t-test after meeting the homogeneity and normality tests. The results showed that the initial abilities of students in both classes (experimental and control) did not show a significant difference, with the same average pretest value, which was 6.66. This shows that the initial conditions of students were relatively equal before being given different treatments. After being given treatment, there was a significant increase in critical thinking skills in the experimental class using the Computational Thinking method, with an average posttest value of 82.93, while the control class using the conventional learning model only reached 50.27. The results of the ANOVA test showed that there was a significant influence of the use of the Computational Thinking method on students' critical thinking skills. The significance value (0.000) is smaller than the significance level (0.05) and the Fcount value of 195.226 is far greater than Ftable (2.90), which means that H₀ is rejected and H₁ is accepted. Thus, it can be concluded that the use of the Computational Thinking method has a significant and positive effect on improving students' critical thinking skills in science learning. This study strengthens the evidence that learning methods that emphasize systematic thinking such as Computational Thinking are effective in improving students' critical thinking skills, involvement, and learning motivation, especially in the context of learning in elementary schools.